A auto-ajuda como interdiscursividade em O alquimista de Paulo Coelho - Ribeiro, Ivi Furloni (2009)
This work, entitled The Self-Help as Interdiscursivity in The Alchemist by Paulo Coelho , has as a goal to establish how the self-help speech crosses interdiscoursively the corpus in analyses as an aesthetical asset/value to the construction of the literary discourse. To develop this study, the readings were based on concepts of the Discourse Analysis theory of the French school such as Interdiscourse, Discoursive Memory and Constitutive Discourse. Furthermore, support was found in the bakhtinian philosophy of language to understand Dialogism. The discoursive analysis of The Alchemist tries to detect how the self-help discourse crosses interdiscoursively the novel and the aesthetical effects built by this same discourse. It can be seen that the self-help discourse grounds the narrative events. Every time Santiago the young pastor weakens in the pursuit of the treasure seen in his recurrent dream, self-help statements are re-stated through the voices of other characters. Those characters are embodied with wisdom and the knowledge Santiago needs to start his journey towards personal fulfillment. Here, the self-help discourse uses constitutive discourses, including its own literary discourse, to be built. Therefore, the literary discourse being analyzed in this work is crossed for several other discourses, such as religious and economical-capitalist ones. When making up stories that create heroes who face same problems as regular human beings, Paulo Coelho stays away from what Russian formalists understand as being good literature . And that is what causes literary critics to consider the Brazilian author as a poor writer/novelist. However, by making his heroes suffer the same males as the ones suffered by the contemporary man, Paulo Coelho attracts the attention of the reader. He or she identifies with the hero feeling insecure, lacking self-confidence, boredom, long for self-fulfillment generated by historic, social and economical events that describe the contemporary world. Paulo Coelho uses the self-help discourse to build his hero because this is what helps the modern man in the search for identity.